Autentisitas Hadis Menurut Syiah - Faza Lulu Arifah (Jurnal Dirosah Islamiyah, 2024)
In the Ahlussunah manhaj, the parameter in interacting with ḥadīṡ is understanding ṡubūt al-Sunnah, namely being able to determine the authenticity or knowing the accuracy of a ḥadīṡ. Apart from Ahlussunah wa al-Jama'ah, there is a large group in Islam called the Shia group which has its own manhaj towards the sunnah or ḥadīṡ Nabī ṣaw. Shia is a firqah in Islam which still exists today. They believe that the Imāmah, like prophethood, does not exist except with a text from Allāh through the word of his Rasūl, or the word of the Imām who is appointed with the text, that is, he will convey the text of the Imām who serves after him. This research aims to determine the authenticity of the ḥadīṡ sanad according to Shia and Shia attitudes towards ḥadīṡ-ḥadīṡ originating from other than Ahl al-Bait. The problem in this research is: What is the authenticity of the ḥadīṡ sanad according to the Shia and what is the Shia's attitude towards ḥadīṡ-ḥadīṡ who come from other than Ahl al-Bait. The type of qualitative research with the main reference is the four ḥadīṡ books which are considered the most ṣaḥīḥ according to Shia, namely: Al-Kafī, Man Lā Yahdurhu al-Faqīh, Tahżīb al-Aḥkām, and al-Istibṣar. The secondary references are the ḥadīṡ books, namely the al-Sittah pole, the book 'Ulūm al-Ḥadīṡ, as well as books on the science of kalam. Data collection in this research is a documentation method. In analyzing the data that has been collected, this research data is then processed and analyzed using a qualitative presentation. This research found that the method commonly used by Shia ulama in conducting research on the authenticity of ḥadīṡ is by providing criteria as stated in the number of ḥadīṡ ulama. However, the difference is that the Shiites have a good standard of narration from the ma'ṣūm Imams among them. Shiites reject ḥadīṡ-ḥadīṡ that do not come from Shiite Imams and Ahl al-Bait. Thus, they do not pay attention to the authenticity of the ḥadīṡ sanad as required by ḥadīṡ experts from Ahlussunnah circles.